Contribution of germline PALB2 variants to an unselected and prospectively registered pancreatic cancer patient cohort in Pakistan. Issue 12 (December 2022) - Muhammad, Noor; Sadaqat, Rida; Naeemi, Humaira; Masood, Iqra; Hassan, Usman; Ijaz, Bushra; Hanif, Faisal; Syed, Aamir A.; Yusuf, Muhammed A.; Rashid, Muhammad U.
Abstract: Background: Partner and localizer of BRCA2 ( PALB2 ) is a pancreatic cancer (PC) susceptibility gene reported in Caucasians. However, limited data are available among Asians. We investigated the contribution of PALB2 germline variants to Pakistani PC patients. Methods: 150 unselected and prospectively enrolled PC patients were comprehensively screened for PALB2 variants, using denaturing high-performance liquid chromatography and DNA sequencing. Novel variants were investigated for their pathogenic effect using in-silico tools. Potentially functional variants were screened in 200 controls. Results: Twenty-two different PALB2 variants were identified. A missense variant (p.Arg37His) was identified in a 48-years-old male patient with a family history of breast cancer. Another missense variant (p.Trp898Arg) was identified in a 48-years-old male patient with a family history of esophageal cancer. A novel 3′ downstream variant (c.∗480A>G) was detected in a 34-years-old female patient with family history of lung cancer. Another novel 3′ downstream variant (c.∗417A>C) was identified in a 41-years-old male patient. All these variants were absent in 200 controls. p.Arg37His and p.Trp898Arg were predicted as likely pathogenic. c.∗417A>C and c.∗480A>G were classified as variants of uncertain significance. Conclusion: This is the first study that suggests a minimal contribution of PALB2 variants to PC risk in Pakistani population.